The Overdense Environments of WISE-Selected, Ultra-Luminous, High-Redshift AGN in the Submillimeter - Jones, Suzy F. (Frontiers in Astronomy and Space Sciences, 2017)
The environments around WISE-selected hot dust obscured galaxies (Hot DOGs) and WISE/radio-selected active galactic nuclei (AGNs) at average redshifts of z = 2.7 and z = 1.7, respectively, were found to have overdensities of companion Submillimeter-selected sources. The overdensities were of 2–3 and 5–6, respectively, compared with blank field submm surveys. The space densities in both samples were found to be overdense compared to normal star-forming galaxies and Submillimeter galaxies (SMGs). All of the companion sources have consistent mid-IR colors and mid-IR to submm ratios to SMGs. Monte Carlo simulations show no angular correlation, which could indicate protoclusters on scales larger than the SCUBA-2 1.5 arcmin scale maps. WISE-selected AGNs appear to be good indicators of overdense areas of active galaxies at high redshift.